PENGARUH LINGKUNGAN KERJA FISIK DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI NEGERI SIPIL PADA DINAS PERHUBUNGAN KOTA DEPOK - Cinta, Mutiara; Apriansyah, Muger (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of the physical work environment and work discipline on employee performance at the Depok City Transportation Service. This research uses a quantitative descriptive method. The population is all employees totaling 50 respondents. Sampling uses quantitative techniques. The data analysis methods used are instrument tests, classical assumption tests, quantitative analysis tests, and hypothesis tests. The t test results show that the physical work environment has a calculated t value of 3.736 > t table 2.011 with a value of Sig. 0.000 < 0.05, this means that the physical work environment partially influences employee performance. Work discipline has a calculated t value of 0.366 < t table 2.011 with a value of Sig. 0.716 > 0.05, this means that work discipline partially has no effect on employee performance. Meanwhile, the results of research using the f test show that the calculated f value > f table or 6.858 > 3.18 with a sig value. 0.002 < 0.05. This means that the physical work environment and work discipline simultaneously influence employee performance. The coefficient of determination test result or R Square is 0.226, meaning that there is an influence between the physical work environment and work discipline which influences employee performance by 22.6% while the remainder (100% - 22.6% = 77.4%) is influenced by other variables that are not researched.